The role of miRNAs in the diagnosis of stable atherosclerosis of different arterial territories: A critical review - Teixeira, Ana Rita; Ferreira, Vera Vaz; Pereira-da-Silva, Tiago; Ferreira, Rui Cruz (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerotic disease is a major cause of morbidity and mortality worldwide. Atherosclerosis may be present in different arterial territories and as a single- or multi-territorial disease. The different phenotypes of atherosclerosis are attributable only in part to acquired cardiovascular risk factors and genetic Mendelian inheritance. miRNAs, which regulate the gene expression at the post-transcriptional level, may also contribute to such heterogeneity. Numerous miRNAs participate in the pathophysiology of atherosclerosis by modulating endothelial function, smooth vascular cell function, vascular inflammation, and cholesterol homeostasis in the vessel, among other biological processes. Moreover, miRNAs are present in peripheral blood with high stability and have the potential to be used as non-invasive biomarkers for the diagnosis of atherosclerosis. However, the circulating miRNA profile may vary according to the involved arterial territory, considering that atherosclerosis expression, including the associated molecular phenotype, varies according to the affected arterial territory. In this review, we discuss the specific circulating miRNA profiles associated with atherosclerosis of different arterial territories, the common circulating miRNA profile of stable atherosclerosis irrespective of the involved arterial territory, and the circulating miRNA signature of multi-territorial atherosclerosis. miRNAs may consist of a simple non-invasive method for discriminating atherosclerosis of different arterial sites. The limitations of miRNA profiling for such clinical application are also discussed.